Evidence that International Undergraduates Can Succeed Academically Despite Struggling with English - Fass-Holmes, Barry; Vaughn, Allison A. (Journal of International Students, 2015)
Many American universities require international applicants whose native language is not English to submit English proficiency exam scores presumably because of proficiency’s potential to predict future academic success. The present study provides evidence, however, that such applicants can succeed academically despite struggling with English. Over 60% of two cohorts of degree-seeking international freshmen at a West Coast public university struggled with English—they failed the university’s English writing proficiency requirement. These international freshmen consequently were required to attend classes in English composition and/or English as a second language. Their average academic marks in these classes were between D+ and C- (18–45% earned less than C), yet their term grade point averages (which excluded the community college classes) were between B and B+. The present findings indicate that these international undergraduates can succeed academically despite apparently inadequate English proficiency.